A different cause for respiratory disorder in children: cases with pulmonary Langerhans cell histiocytosis. (3rd July 2015) - Asilsoy, Suna; Yazici, Nalan; Demir, Senay; Erbay, Ayse; Koçer, Emrah; Sarıalioğlu, Faik
Abstract: Background and Aims: In children, complaints of a respiratory disorder are very frequent. Etiology of respiratory illness is a broad spectrum that varies from a simple viral infection to a malignant disorder. Pulmonary Langerhans cell histiocytosis (PLCH) is one of these entities and it is truly rare in children. The aim of this study is to evaluate our patients with PLCH. Methods: Patients who had been diagnosed with PLCH were retrospectively evaluated. Features of medical history, onset of the complaints, date of the diagnosis, chest X‐Ray and computed tomography (CT) findings, histopathology and other laboratory investigations were considered. Results: There were four cases with PLCH. All of them were male, ages were between 5 months and 16 years. In three cases, major complaints were chronic respiratory problems whereas in one of them there was acute respiratory distress beginning with cough and leading to pneumothorax. In all of the cases, multisystemic involvement was prominent. The diagnosis was proven by histopathology in all of the cases. In two children with smaller age, skin involvement was detected. Time from complaint to diagnosis was minimum 3 months and maximum 3 years. Conclusion: PLCH is a rare disorder in children. Pulmonary involvement is generally a component of systemic involvement but in many cases it might have been detected with early respiratory complaints. So, children with chronic respiratory problems should be carefully evaluated and should be followed up for rare entities like PLCH.